Gemcitabine-associated reversible encephalopathy a case report - (:unkn) unknown (My University, 2002)
In this report, we present a ten-year-old male patient with metastatic Ewing's sarcoma who developed encephalopathy after treatment with gemcitabine, and his rapid recovery after discontinuation of the drug.
Keywords: Gemcitabine; Neurotoxicity; Pediatric cancer